Polysome Profiling Proves Impaired IL-10 and Caspase-8 Translation in PBMCs of Hemodialysis Patients - Amanda Dawood; Roman Fiedler; Silke Markau; Matthias Girndt; Christof Ulrich (Biomolecules)
Triggered by uremic intoxication, a surplus of inflammatory mediators is present in the serum of hemodialysis (HD) patients. Anti-inflammatory counterbalancing mechanisms initiated by interleukin-10 (IL-10) and caspase-8 (Casp-8) appear to be disturbed. Earlier observations let us suppose that translational rather than transcriptional mechanisms are responsible for this effect. Therefore, we investigated the polysome profiling of isolated PBMCs to study gene-specific mRNAs attached to monosomes and polysomes in HD patients (n = 42), patients with lipid disorder and normal renal function (LD, n = 10) and healthy control subjects (CO, n = 9). CRP (C-reactive protein) as a marker of inflammation was significantly elevated in HD and LD patients compared to CO subjects. NGAL (neutrophil-associated lipocalin), a potential marker of kidney disease and inflammation was increased in HD versus LD and CO. LD patients, however, had significantly higher proteosomal IL-10 and Casp-8 activities. LD and HD are two high cardiovascular risk groups with microinflammation. Lower translational activities of IL-10 and Casp-8 mRNAs in HD may be the result of a weak anti-inflammatory response potentially associated with the uremic immune defect.